PENGARUH NILAI EKSPOR BATUBARA, PRODUKSI BATUBARA DAN SUMBER DAYA MANUSIA TERHADAP PENDAPATAN SEKTOR PERTAMBANGAN - A.Bagas Windu Panji Nata; Nairobi; Darmawan, Arif (Elastisitas : Jurnal Ekonomi Pembangunan, 2023)
This study intends to examine how the value of coal exports, coal production, and human resources all affect the mining industry's revenue. According to the Central Statistics Agency's estimates for 2021, Indonesia is the third largest coal production in the world. Secondary data on the value of coal exports, coal output, and human resources are used in this study. This study uses data from the Indonesian statistical center and covers the period from the first quarter of 2012 to the fourth quarter of 2021. Descriptive quantitative research is the type that was used in this investigation. The vector autoregression (VAR) approach, which employs the stationarity test, optimal lag test, VAR stability test, cointegration test, and Granger causality test, is utilized to analyze the data. EViews 10 is the data processing application tool used in this investigation. The studies' findings indicate that the value of coal exports makes a significant financial contribution to Indonesia's mining industry. The contribution made by human resources is the least.